New Nomenclature for Nonalcoholic Fatty Liver Disease: Understanding Metabolic Dysfunction-Associated Steatotic Liver Disease, Metabolic Dysfunction- and Alcohol-Associated Liver Disease, and Their Implications in Clinical Practice - Canivet, Clémence M.; Boursier, Jérôme; Loomba, Rohit (Seminars in Liver Disease, 2024)
In June 2023, under the patronage of the American Association for Study of Liver Disease, the European Association for Study of the Liver, and the Asociación Latinoamericana para el Estudio del Hígado with the involvement of 236 participants from around the world, a new nomenclature and definition for nonalcoholic fatty liver disease (NAFLD) has been proposed. Metabolic dysfunction-associated steatotic liver disease (MASLD) was defined as presence of hepatic steatosis and at least one of the cardiometabolic risk factors with alcohol intake less than 140 g/wk for women and 210 g/wk for men and no other causes of steatosis. A new entity called combined metabolic dysfunction- and alcohol-associated liver disease (MetALD) was created outside of pure MASLD for patients with metabolic dysfunction and alcohol intake greater than that allowed for MASLD (i.e., 140–350 g/wk for women and 210–420 g/wk for men). Recent studies have confirmed a 95% overlap between NAFLD and the new MASLD diagnostic criteria. Natural history, biomarkers, and thresholds of alcohol intake in MetALD group remains to be studied and validated.
Keywords: NAFLD; MASLD; MetALD; nomenclature; cardiometabolic